Analisis Tingkat Risiko Paparan NOx Terhadap Pekerja Di Gardu Tol Akibat Volume Kendaraan di Pintu Tol Jagorawi, Bogor - Astri Salatin; Chusnul Arif; Namira Dita Rachmawati (Jurnal Teknik Sipil dan Lingkungan, 2019)
Bogor as tourist destination at weekend bear quite high vehicles volume. The purpose of this research was to analyze corelation between vehicles volume at highways gate and NOx exposure from the vehicles. By knowing the average concentration of NOx exposure level pollution risk to the health of highway gate worker could be analyzed. This research using Griess Saltzman method referring to SNI 19-7119.2-2005 using some equipment like impinger. The result showed that type of vehicle that produced the highest amount of NOx pollutant was vehicles with diesel engine, and the gate with highest NOx concentration was gate 08 with NOx concentration value 40.008 µg/m3 at 09.00-10.00. Risk quotient (RQ) to the workers with weighed 65-90 kg and had been working for 25 years was 0.041950 and it was RQ < 1. It meaned that the average pollution caused by NO2 at the highways gate does not affect workers and workers does not cause any health risk because RQ < 1. For the next research, it would be recommended to conduct on O3 and NO3, because those compounds are easily reacted with NOx in the air.